Frailty in elderly patients with acute myocardial infarction - Kamilya Kedelbaeva; Salim Berkinbaev; Gulnar Dzhunusbekova; Meyramgul Tundybaeva; Aliya Kabdulkayeva (National Scientific Medical Center, 2022)
In recent years, there has been increasing interest in the frailty as a prognostic factor of acute myocardial infarction in elderly patients. Frailty is an important prognostic marker of frequent complications, readmission to hospital, high hospital mortality and major cardiovascular events in elderly patients with acute myocardial infarction. This category of persons is often not allowed to undergo invasive interventions and are often excluded from the recommended treatment, and they tolerate cardiac surgery worse, recovery from illness is slower, functionality decreases, then disability and death develop.       The present review aims to investigate the impact of frailty on management of elderly patients with acute myocardial infarction (AMI).     To analyze the literature, we searched for information on this issue in PubMed / MEDLINE, PMC, Web of Science, Scopus, The Сocrane Library. The search depth was 15 years: from 2006 to 2021.       One of the important factors in improving clinical outcomes, improving the quality of life in elderly patients with acute myocardial infarction is the early detection of frailty. Frailty assessment is a valuable tool for risk stratification that can be helpful to clinicians in deciding the optimal pathway for management and treatment strategies. Risk prediction is also important for deciding secondary prevention and cardiac rehabilitation measures in the elderly with acute myocardial infarction.